Karawitan Composition “Bhuana Santhi” | Komposisi Karawitan “Bhuana Santhi” - Kadek prema Nandayana; Saptono - (Pusat Penerbitan LPPMPP ISI Denpasar, 2023)
Bhuana Santhi is a work by tabuh telu lelambatan creations inspired by community activities doing gotong royong, precisely in Lepang Customary Village, Klungkung Regency. This work is still guided by the pattern of traditional work and a little innovation in some parts. As in the section before entering into the pattern of the stone shades played kebyar which according to the stylist an innovation. This work illustrates a sense of togetherness between each other when doing mutual cooperation activities related to piodalan events, namely at Dalem Sila Pegat Temple, Lepang Customary Village, Klungkung Regency. Before the ceremony takes place usually five or six days before, the people of Lepang Indigenous Village carry out mutual cooperation activities both from krama lanang (male) and krama istri (female). The method of creation used in Bhuana Santhi's work is Panca Sthiti Ngawi Sani by I Wayan Dibia which includes the ngawirasa (Inspiration) stage, the ngawacak (exploration) stage, the ngarencana (conception), the ngawangun (execution), and the stage of worship, (production), making it easier for stylists to realize the work of Bhuana Santhi. Bhuana Santhi uses media revealed Gamelan Gong Kebyar. The structure of Bhuana Santhi consists of three parts, namely the fumigation, manning and the drilling and the duration of the entire Bhuana Santhi work is 12 minutes.